2015
DOI: 10.1016/j.celrep.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 Coordinately Regulates Gene Expression and the Chromatin Landscape during Neurogenesis

Abstract: SummaryThe proneural transcription factor Ascl1 coordinates gene expression in both proliferating and differentiating progenitors along the neuronal lineage. Here, we used a cellular model of neurogenesis to investigate how Ascl1 interacts with the chromatin landscape to regulate gene expression when promoting neuronal differentiation. We find that Ascl1 binding occurs mostly at distal enhancers and is associated with activation of gene transcription. Surprisingly, the accessibility of Ascl1 to its binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
150
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 42 publications
18
150
0
Order By: Relevance
“…The proneural bHLH transcription factor Ascl1 (closely related to Atoh1) is known to be a pioneer factor, capable of binding to nucleosomal-occluded DNA (28,29) and promoting chromatin accessibility at the regulatory regions of its targets (29). However, pioneer activity remains to be determined for Atoh1.…”
Section: Chromatin Landscape and Epigenetic Modificationsmentioning
confidence: 99%
“…The proneural bHLH transcription factor Ascl1 (closely related to Atoh1) is known to be a pioneer factor, capable of binding to nucleosomal-occluded DNA (28,29) and promoting chromatin accessibility at the regulatory regions of its targets (29). However, pioneer activity remains to be determined for Atoh1.…”
Section: Chromatin Landscape and Epigenetic Modificationsmentioning
confidence: 99%
“…Examination of chromatin accessibility by mapping DNase I hypersensitive sites (DHSs) genome wide, in a large array of stem cells and their more committed progeny, has revealed that most DHSs are cell type specific. These studies have also shown that lineage specification and maturation are characterized by a general condensation of chromatin, paralleled by a selective de novo formation of open chromatin regions (Stergachis et al 2013;LaraAstiaso et al 2014;Raposo et al 2015). Interestingly, the resulting differences in the chromatin landscape that these changes bring can accurately cluster cells according to their lineage relationships (Song et al 2011;Stergachis et al 2013).…”
mentioning
confidence: 99%
“…These results propose a model in which Mash1/Ascl1 integrates inputs from both stimulatory and inhibitory signals and converts them into a transcriptional program activating adult neural stem cells (Andersen et al 2014). The temporal progression of the transcriptional program seems to be linked to the chromatin landscape at target regions as Mash1/Ascl1 promotes chromatin accessibility during neurogenesis (Raposo et al 2015).…”
Section: Transcription Factors and Neurogenesismentioning
confidence: 99%